2019
DOI: 10.1038/s41587-019-0260-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted isolation and cultivation of uncultivated bacteria by reverse genomics

Abstract: Most microorganisms from all taxonomic levels are uncultured. Single-cell genomes and metagenomes continue to increase the known diversity of Bacteria and Archaea, but while 'omics can be used to infer physiological or ecological roles for species in a community, most of those hypothetical roles remain unvalidated. Here we report an approach to capture specific microorganisms from complex communities into pure cultures using genome-informed antibody engineering. We apply our reverse genomics approach to isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
296
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(302 citation statements)
references
References 93 publications
6
296
0
Order By: Relevance
“…Cross et al . () showed that related SN01 bacteria may be isolated by immuno‐targeting cell surface proteins used by SN01 for attachment to prey bacteria. The blooming of these bacteria during famine periods indicates they may at least benefit from the demise of other populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cross et al . () showed that related SN01 bacteria may be isolated by immuno‐targeting cell surface proteins used by SN01 for attachment to prey bacteria. The blooming of these bacteria during famine periods indicates they may at least benefit from the demise of other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Among CPR Bacteria, Gracilibacteria have been shown to use a different genetic code and are believed to survive through a highly syntrophic or parasitic lifestyle (Hanke et al, 2014;Anantharaman et al, 2016;Probst et al, 2018). Cross et al (2019) showed that related SN01 bacteria may be isolated by immuno-targeting cell surface proteins used by SN01 for attachment to prey bacteria. The blooming of these bacteria during famine periods indicates they may at least benefit from the demise of other populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to this wealth of information, one of the most beneficial outcomes of shotgun metagenomic projects is the ability to assemble high quality, complete or nearly-complete, genomes from organisms not yet amenable to cultivation practices (Tyson et al , 2004;Luo et al , 2012) . And indeed, such metagenome-assembled-genomes (MAGs) have provided information leading to the cultivation of organisms of interest (Gutleben et al , 2018;Cross et al , 2019;Imachi et al , 2019) , along with the discoveries of new metabolic processes (Daims et al , 2015) , novel insights into the ecology and evolution of globally abundant groups (Delmont et al , 2018) , and uncovering a wide diversity of novel Phylum-level lineages that have restructured the current understanding of the tree of life (Brown et al , 2015;Hug et al , 2016) .…”
Section: Introductionmentioning
confidence: 99%